2010
DOI: 10.1002/cne.22440
|View full text |Cite
|
Sign up to set email alerts
|

Retinal photoreceptors of two subterranean tuco‐tuco species (Rodentia, Ctenomys): Morphology, topography, and spectral sensitivity

Abstract: Traditionally, vision was thought to be useless for animals living in dark underground habitats, but recent studies in a range of subterranean rodent species have shown a large diversity of eye features, from small subcutaneous eyes to normal-sized functional eyes. We analyzed the retinal photoreceptors in the subterranean hystricomorph rodents Ctenomys talarum and Ctenomys magellanicus to elucidate whether adaptation was to their near-lightless burrows or rather to their occasional diurnal surface activity. B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 51 publications
(83 reference statements)
1
23
0
2
Order By: Relevance
“…These results reinforce the statement that C. aff knighti displays much less polymorphism in rhythmic patterns than other subterranean rodents [21]. Some morphological features, such as the size of the eye and structure of the retina, also distinguish ctenomyids from other subterranean rodents [52]. Remarkably, tuco-tucos forage aboveground [10], [11] more frequently than other strictly subterranean rodents [53], [47] and it has been shown that these surface excursions ensure photic entrainment of their circadian oscillators [12].…”
Section: Discussionsupporting
confidence: 79%
“…These results reinforce the statement that C. aff knighti displays much less polymorphism in rhythmic patterns than other subterranean rodents [21]. Some morphological features, such as the size of the eye and structure of the retina, also distinguish ctenomyids from other subterranean rodents [52]. Remarkably, tuco-tucos forage aboveground [10], [11] more frequently than other strictly subterranean rodents [53], [47] and it has been shown that these surface excursions ensure photic entrainment of their circadian oscillators [12].…”
Section: Discussionsupporting
confidence: 79%
“…In the majority of rodent taxa, S-cones have blue sensitivity, depending on the amino acids present at a few key positions. Degus’ UV cones were confirmed by electroretinography (ERG) (Chavez et al 2003), behavior, immunocytochemistry (Jacobs et al 2003), and partial opsin sequences (Schleich et al 2010). Why some rodents have UV versus violet-sensitive cones is not known, but it is speculated to be useful for sexual selection, navigation, foraging, object, and urine detection (Chavez et al 2003; Goldsmith 1994).…”
Section: Uses Of the Degu As An Animal Modelmentioning
confidence: 99%
“…Many species, for example, possess visual pigments with λ max below 400 nm, and the resultant UV-sensitivity is relatively widespread among invertebrates [68], birds, fish, reptiles and amphibians [9,10]. Among mammals, such UV-sensitive visual pigments are relatively rare and have only been described in some rodents [1118], a mole [19], several marsupials [2023] and some bats [2427]. Such animals have lenses that, unlike those of humans, transmit short wavelengths well.…”
Section: Introductionmentioning
confidence: 99%